2006
DOI: 10.1590/s0100-879x2006001000012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treadmill gait on bone markers and bone mineral density of quadriplegic subjects

Abstract: Quadriplegic subjects present extensive muscle mass paralysis which is responsible for the dramatic decrease in bone mass, increasing the risk of bone fractures. There has been much effort to find an efficient treatment to prevent or reverse this significant bone loss. We used 21 male subjects, mean age 31.95 ± 8.01 years, with chronic quadriplegia, between C4 and C8, to evaluate the effect of treadmill gait training using neuromuscular electrical stimulation, with 30-50% weight relief, on bone mass, comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 33 publications
(38 reference statements)
1
31
0
1
Order By: Relevance
“…The positive muscle alterations provided by NMES also can benefit the oxygen consumption [5,10,12,17] and bone mass of individuals with spinal cord injury [2,6,19].…”
Section: Introductionmentioning
confidence: 99%
“…The positive muscle alterations provided by NMES also can benefit the oxygen consumption [5,10,12,17] and bone mass of individuals with spinal cord injury [2,6,19].…”
Section: Introductionmentioning
confidence: 99%
“…These patients also had an efficient increase in bone mineral density -in that, 81.8% of subjects presented a significant increase in bone formation and 66.7% had a marked decrease in bone resorption markers, thus reducing the risk of fractures in osteoporotic bones (6) . Although there is scientific evidence that patients with cerebral and spinal injuries benefit from NMES in the rehabilitation of muscular and cardio respiratory parameters (13) , to date there has been no report on the effects of NMES on the low urinary tract function.…”
Section: Discussionmentioning
confidence: 95%
“…Treadmill gait training with neuromuscular electrical stimulation (NMES) in quadriplegic subjects is capable of improving movements (even quadriplegics with complete lesions), metabolic and cardio respiratory responses and bone mineral density. It was reported that these findings are associated with a better coordination of voluntary and autonomic functions of muscles and nervous pathways; however, there is no unanimous understanding on how and why it happens (4)(5)(6) . To date, the effects NMES on the inferior urinary tract have never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…It would be rather relevant to take a closer look on the knees of tetraplegic patients through magnetic resonance image (MRIs), in order to obtain a broader picture of their rehabilitation program, following previous studies showing the benefits obtained with treadmill gait and NMES. 1,6,18 …”
Section: Objectivesmentioning
confidence: 99%